Impairment of Cardiac Autonomic Nerve Function in Pre-school Children With Intractable Epilepsy - Yang, Zhao; Cheng, Tung-Yang; Deng, Jin; Wang, Zhiyan; Qin, Xiaoya; Fang, Xi; Yuan, Yuan; Hao, Hongwei; Jiang, Yuwu; Liao, Jianxiang; Yin, Fei; Chen, Yanhui; et al. (Frontiers in Neurology, 2021)
Abstract Objective: Intractable epilepsy and uncontrolled seizures could affect cardiac function and autonomic nerve system with negative impact on children growth. The aim of this study was to investigate the variability and complexity of cardiac autonomic function in pre-school children with pediatric intractable epilepsy (PIE). Methods: 24-h holter electrocardiograms (ECG) from 93 patients and 46 healthy control subjects aged 3-6 years were analyzed by the methods of traditional heart rate variability (HRV), multiscale entropy (MSE) and Kurths-Wessel symbolization entropy (KWSE). Receiver operating characteristic (ROC) curve analysis was used to estimate the overall discrimination ability. Net reclassification improvement (NRI) and integrated discrimination improvement (IDI) models were also analyzed. Results: Pre-school children with PIE had significantly lower HRV measurements than healthy controls in time domain (Mean_RR, SDRR, RMSSD, pNN50) and frequency domain (VLF, LF, HF, LF/HF, TP). For the MSE analysis, area 1_5 in wake state was lower and area 6_15, area 6_20 in sleep state were higher in PIE with significant statistical difference. KW symbolization entropy in PIE group was also inferior to that in healthy controls. In ROC curve analysis, pNN50 had the greatest discriminatory power for PIE. Based on both NRI and IDI models, the combination of MSE indices (Wake: area1_5 and Sleep: area6_20) and KWSE (m = 2, τ = 1, α = 0.16) with traditional HRV measure had greater discriminatory power than any of the single HRV measure. Significance: Impaired heart rate variability and complexity were found in pre-school children with PIE. HRV, MSE and KWSE could discriminate patients with PIE from subjects with normal cardiac complexity. These findings suggested that MSE and KW symbolization method may be helpful for assessing and understanding heart rate dynamics in younger children with epilepsy.